The big data security challenge. Issue 1 (January 2015) - Lafuente, Guillermo
Abstract : Enterprises are fast realising the potential that big data can hold for their organisations in terms of marketing and customer service, but there is a fine line between the legitimate use of that data and customer privacy. There is a fine line between the legitimate use of big data and customer privacy. And before any big data projects begin, organisations should have the right mechanisms in place to protect that data from the outset. People across the organisation must understand the consequences of not treating customer and employee data with proper consideration. And when it comes to security, there are plenty of steps that can be taken to help make sure personal information is treated with due care, explains Guillermo Lafuente of MWR InfoSecurity.